The diverse N-glycosylation profiles of CD4+CD25- and CD4+CD25+ T cells in Hashimoto’s thyroiditis - Trzos, Sara; Szewczyk, Marta; Link-Lenczowski, Paweł; Sokołowski, Grzegorz; Trofimiuk-Müldner, Małgorzata; Bocian, Katarzyna; Pocheć, Ewa (Frontiers in Immunology, 2025)
Hashimoto’s thyroiditis (HT) is one of the most common organ-specific autoimmune diseases, characterized by chronic thyroid gland inflammation. Helper T (Th) CD4+ cells, whose surface receptors are highly glycosylated, are involved in the pathomechanism of HT. Our study aimed to characterize N-glycosylation profiles in two pools of CD4+ T cells, defined by the expression of CD25+ late activation marker (CD4+CD25+) and CD25-negative cells (CD4+CD25-) in HT. Two study groups were recruited: HT1 with elevated thyroid autoantibodies and TSH level within the normal range without hypothyroidism, and HT2, hypothyroid HT patients, adequately metabolically controlled while on L-thyroxine replacement therapy, and healthy subjects to the control group (CTR). N-glycans from CD4+ cell proteins, released using N-glycosidase F, were analyzed by MALDI-Tof mass spectrometry. RT-qPCR was used to determine the expression of selected glycogenes. We found significant differences in the glycome of CD4+CD25- and CD4+CD25+ cells. In homeostasis (CTR), a predominance of complex-type glycans was observed in CD4+CD25- cells, whereas the oligomannose-type structures prevail in CD4+CD25+ lymphocytes. In autoimmunity and progressive thyroid dysfunction, the rearrangement of N-glycans in Th cells was observed, in opposite directions in the CD4+ pools. Complex-type structures are replaced by oligomannose forms in CD4+CD25- in the HT1 group, while in HT2, a restoration of glycosylation profile to the level of CTR was detected. CD4+CD25+ cells accelerated complex-type synthesis in HT1, which was normalized in HT2 patients. Changes in the profile of N-linked glycans are partially reflected in the expression of mannosidases and glycosyltransferases. Our study demonstrates for the first time the diverse N-glycosylation profiles in CD4+CD25- and CD4+CD25+ cells, and the rearrangement of N-glycan structures specific for each pool of Th cells in HT. Further studies are needed to determine the functional aspect of the identified N-glycosylation changes during thyroid autoimmunity.